Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

The vertices of a hyperbola are located at [tex](3,-6)[/tex] and [tex](3,6)[/tex]. The foci of the same hyperbola are located at [tex](3,-10)[/tex] and [tex](3,10)[/tex]. What is the equation of the hyperbola?

A. [tex]\frac{y^2}{36} - \frac{(x-3)^2}{64} = 1[/tex]
B. [tex]\frac{(y-3)^2}{36} - \frac{x^2}{64} = 1[/tex]
C. [tex]\frac{(y-3)^2}{64} - \frac{x^2}{36} = 1[/tex]
D. [tex]\frac{y^2}{64} - \frac{(x-3)^2}{36} = 1[/tex]


Sagot :

To find the equation of the hyperbola based on the given vertices and foci, follow these steps:

1. Determine the center of the hyperbola:
The vertices are located at \((3, -6)\) and \((3, 6)\). The center of the hyperbola is the midpoint of the vertices.

Midpoint [tex]\[ \left( \frac{x_1 + x_2}{2}, \frac{y_1 + y_2}{2} \right) = \left( \frac{3 + 3}{2}, \frac{-6 + 6}{2} \right) = (3, 0) \][/tex]

2. Determine the distance between the vertices:
The distance between the two vertices is the length of the transverse axis, which is \(2a\). From \((3, -6)\) to \((3, 6)\), the distance is 12 units.
[tex]\[ 2a = 12 \implies a = \frac{12}{2} = 6 \][/tex]

3. Determine the distance between the foci:
The foci are located at \((3, -10)\) and \((3, 10)\). The distance between the foci is \(2c\). From \((3, -10)\) to \((3, 10)\), the distance is 20 units.
[tex]\[ 2c = 20 \implies c = \frac{20}{2} = 10 \][/tex]

4. Determine \(b\):
Use the relationship between \(a\), \(b\), and \(c\) for hyperbolas:
[tex]\[ c^2 = a^2 + b^2 \][/tex]
Substituting the known values:
[tex]\[ 10^2 = 6^2 + b^2 \implies 100 = 36 + b^2 \implies b^2 = 64 \][/tex]

5. Write the equation of the hyperbola:
Since the hyperbola opens vertically (as indicated by the vertical difference in the vertices and foci), its standard form is:
[tex]\[ \frac{(y - k)^2}{a^2} - \frac{(x - h)^2}{b^2} = 1 \][/tex]
Here, \(h = 3\), \(k = 0\), \(a = 6\), and \(b^2 = 64\):
[tex]\[ \frac{(y - 0)^2}{6^2} - \frac{(x - 3)^2}{64} = 1 \implies \frac{y^2}{36} - \frac{(x - 3)^2}{64} = 1 \][/tex]

Thus, the correct equation of the hyperbola is:
[tex]\[ \boxed{\frac{y^2}{36} - \frac{(x - 3)^2}{64} = 1} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.